The Importance of Interdiscipliner Studies in Engineering Education - Guney, Deniz (INT INST INFORMATICS & SYSTEMICS, 2011)
As the world's dependence on technology increases, there is no question that the demand for engineers is increasing. Engineering is a key component of innovation and technological society. Engineering education system is the most important subject for the future of the society. For large scale projects, many different professions such as architects, civil engineers, mechanical engineers, electrical engineers, consultants, state officers, bankers etc. have to work together. In the professional life, engineer generally has to overcome very sophisticated problem during execution stage of the project. In order to solve those problems, it is necessary to know point of view of different professions. Those problems can be solved by engineers have broader perspective. This perspective can be given during education period. However, existing education system leads students to go into technical details of specific problems not common in practice. In this paper, it is aimed to investigate the lack of interdisciplinary studies during university education in Turkey and the world. In addition to this in order to decrease unemployment rate in university graduate students, the qualification of the students must be increased. This study mainly focused on the two aspects: theoretical discussions and exemplification of practical concern of interdisciplinary education.
Keywords: Education; interdiscipliner; engineering; architecture; university; GRADUATE-EDUCATION; Computer Science